The Macquarie Dictionary, its History and its Editorial Practices - Delbridge, Arthur; Butler, Susan (Lexikos, 1999)
The Macquarie Dictionary, first published in Sydney in 1981, was intended to be the first comprehensive dictionary of Australian English. Now in its third edition it has been widely adopted by institutions and the general community as the national dictionary. This paper traces its development from a difficult birth to its present maturity, from a large set of cards to an electronic database, from a single book to a lexicographic library. The rationale and the methodology are laid out along with an account of the reception given to the dictionary in Australia and internationally.Keywords: dictionary; lexicography; macquarie dictionary; australianness; australianise; australian english; national dictionaries; phonology; international phonetic alphabet; lexical labels; lexicographic style; language style; colloquial; aboriginal words; electronic database; corpus; citation